2022
DOI: 10.3390/ijerph19127369
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Its Barriers and Facilitators among University Students in Qatar: A Cross-Sectional Study

Abstract: Physical inactivity is a leading risk factor for non-communicable diseases worldwide. This study investigated physical activity (PA) level among university students in Qatar and assessed other lifestyle and demographic factors associated with PA. A cross-sectional study was conducted between February 2017 and February 2018. A self-administered questionnaire, comprising questions from the International Physical Activity Questionnaire and other validated questionnaires, was used to assess PA and other lifestyle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 33 publications
3
9
0
1
Order By: Relevance
“…This finding supports previous research [64,65], indicating that the proximity of university campuses to parks (i.e., green spaces) may encourage staff and students to engage in more routine PA. This is possibly because parks offer people the chance to spend ample time with colleagues, friends, or family away from the clamour and hassles in the city, bond with nature and engage in PA [66].…”
Section: Environmental Context and Resourcessupporting
confidence: 90%
“…This finding supports previous research [64,65], indicating that the proximity of university campuses to parks (i.e., green spaces) may encourage staff and students to engage in more routine PA. This is possibly because parks offer people the chance to spend ample time with colleagues, friends, or family away from the clamour and hassles in the city, bond with nature and engage in PA [66].…”
Section: Environmental Context and Resourcessupporting
confidence: 90%
“…Prevalence patterns of people meeting the WHO PA guidelines by age group (adults vs. children) and sex during the pandemic are likely due to the persistence of previously identified barriers to PA, such as lack of time, social support, and motivation. It has been demonstrated that personal and social barriers to PA are higher among females than males in several countries (13,(53)(54)(55)(56)(57). These barriers include the traditional roles and family obligations ascribed to women, as well as a lack of social support, less freedom, and less access to facilities to engage in PA as compared to males.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with an HOMA-IR less than or equal to 1.85 were categorized as IS, whereas those with an HOMA-IR greater than 1.85 were categorized as IR. Physically active participants were identified as those who walk at least two days per week for more than 150 min [24][25][26][27]. Inclusion criteria included young (20-30 years old), lean/overweight (BMI: 20-30 kg/m 2 ), healthy (no chronic diseases) individuals.…”
Section: Data Source and Study Participantsmentioning
confidence: 99%
“…Among all participants, 51.5% were males and 54.6% were IS, including 22.5% sedentary (ISS) and 32.2% active (ISA), whereas 45.4% were IR, including 24.4% sedentary (IRS) and 20.9% active (IRA) (Figure 1). identified as those who walk at least two days per week for more than 150 min [24][25][26][27].…”
Section: Data Source and Study Participantsmentioning
confidence: 99%